PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR SUHU DAN KALOR - Sri Utami Kholila Mora Siregar (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2017)
This research aims to (1) improve the result of students’ physics learning on the subject of temperature and calority of the eleventh grade students of SMA Negeri 5Padangsidimpuan Academic Year 2017, (2) to know the learning outcomes about the application of problem posing learning model in heat and temperature subjects as direct impact (3) to know the learning outcomes about the application of problem posing learning model in heat and temperature subjects as indirect impact to the ability and attitude of the eleventh grade students of SMA Negeri 5 Padangsidimpuan Academic Year 2017. The research method used a classroom action research using two cycles on temperature and heat material subjects. The subject of this research is the students of the eleventh grade of SMA Negeri 5 Padangsidimpuan, which amounting to thirty students. The conclusions of this study are (1) The direct impact on the application of problem posing learning model on heat and temperature subject on the eleventh grade students of SMA Negeri 5 Padangsidimpuan (2) The indirect impact on the application of problem posing learning model on calority and temperature subject to improve the eleventh grade students’ learning result of SMA Negeri 5 Padangsidimpuan. All students know that learning is not just about what is learned but why and how to learn it. Students can also communicate with their teachers and friends at school. The process of information exchange, the students have self- confidence and self-esteem so that they have positive effect on the motivation and scientific attitudes, as well as acquire the learning skills and the life skill from what they find in the learning process.